Europejskie performanse Ive Tabara – od dyskursu politycznego do metanarracji - Wachowski, Jacek (Slavia Occidentalis, 2017)
The article is an attempt to analyze the works of Ive Tabar – one of the most interesting Slovenian artists (relatively little known) working on the borderline of body art and performance art. On the one hand, Tabar’s works refer to loud experiments – undertaken on the basis of body art in 60’s, 70’s and 80’s. On the other hand, they are seeking their own language and new communication strategies with the viewers. Tabar’s works are both personal acts and political declarations (regarding the future of Slovenia). In this sense, they can be understood as a return to the concept (that had been developed in Europe and America in the second half of the twentieth century) of engaging art for public activity. Tabar uses this tradition in its own and unique way. He creates metanarratives works that combine the poetics of political and social protest with a radical body art-style experiment. He shows the way how art can contribute a political life.Key words: Slovenian performance, Ive Tabar, body art, performing arts.